Caribbean blacks and West African blacks: A study in attitude similarity and change - Green, Helen Bagenstose (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Attitudinal responses from a sample of Caribbean Black school students in Trinidad are compared with responses from West African Black students in English-speaking Gambia and with matched East Indian students from the other co-culture in Trinidad. Findings from open-ended questionnaires show the two Black samples to differ from the East Indian sample in the greater priority given to social concerns. Responses related to their initiative and goals in manipulating the environment show the Caribbean Black sample to exceed both the West African Black sample and the East Indian sample. Responses related to personality expansion show both the Caribbean Black sample and the East Indian sample to be more outgoing, secure, and realistic than the West African sample.